DEP domain–containing mTOR–interacting protein suppresses lipogenesis and ameliorates hepatic steatosis and acute‐on‐chronic liver injury in alcoholic liver disease. Issue 2 (21st May 2018) - Chen, Hanqing; Shen, Feng; Sherban, Alex; Nocon, Allison; Li, Yu; Wang, Hua; Xu, Ming‐Jiang; Rui, Xianliang; Han, Jinyan; Jiang, Bingbing; Lee, Donghwan; Li, Na; et al.
Abstract : Alcoholic liver disease (ALD) is characterized by lipid accumulation and liver injury. However, how chronic alcohol consumption causes hepatic lipid accumulation remains elusive. The present study demonstrates that activation of the mechanistic target of rapamycin complex 1 (mTORC1) plays a causal role in alcoholic steatosis, inflammation, and liver injury. Chronic‐plus‐binge ethanol feeding led to hyperactivation of mTORC1, as evidenced by increased phosphorylation of mTOR and its downstream kinase S6 kinase 1 (S6K1) in hepatocytes. Aberrant activation of mTORC1 was likely attributed to the defects of the DEP domain‐containing mTOR‐interacting protein (DEPTOR) and the nicotinamide adenine dinucleotide–dependent deacetylase sirtuin 1 (SIRT1) in the liver of chronic‐plus‐binge ethanol‐fed mice and in the liver of patients with ALD. Conversely, adenoviral overexpression of hepatic DEPTOR suppressed mTORC1 signaling and ameliorated alcoholic hepatosteatosis, inflammation, and acute‐on‐chronic liver injury. Mechanistically, the lipid‐lowering effect of hepatic DEPTOR was attributable to decreased proteolytic processing, nuclear translocation, and transcriptional activity of the lipogenic transcription factor sterol regulatory element‐binding protein‐1 (SREBP‐1). DEPTOR‐dependent inhibition of mTORC1 also attenuated alcohol‐induced cytoplasmic accumulation of the lipogenic regulator lipin 1 and prevented alcohol‐mediated inhibition of fatty acid oxidation. Pharmacological intervention with rapamycin alleviated the ability of alcohol to up‐regulate lipogenesis, to down‐regulate fatty acid oxidation, and to induce steatogenic phenotypes. Chronic‐plus‐binge ethanol feeding led to activation of SREBP‐1 and lipin 1 through S6K1‐dependent and independent mechanisms. Furthermore, hepatocyte‐specific deletion of SIRT1 disrupted DEPTOR function, enhanced mTORC1 activity, and exacerbated alcoholic fatty liver, inflammation, and liver injury in mice. Conclusion : The dysregulation of SIRT1–DEPTOR–mTORC1 signaling is a critical determinant of ALD pathology; targeting SIRT1 and DEPTOR and selectively inhibiting mTORC1–S6K1 signaling may have therapeutic potential for treating ALD in humans. (Hepatology 2018).